PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONCIBILITY DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI - Ade Kurniawan, Dewi Saptantinah Puji Astuti & Fadjar Harimurti (Universitas Slamet Riyadi, 2019)
This study aims to determine the effect of leverage (DER) and liquidity (CR) on CSR (Corporate Social Responcibility) disclosure with institutional ownership as a moderating variable. This study uses quantitative data types derived from the annual report and company sustainability report published on the website of BEI (www.idx.co.id) and website of each company. The population in this study as many as 45 companies contained in the index LQ45 BEI , sampling technique using purposive sampling that is a number of 11 companies selected. Data analysis techniques used classical assumption test, multiple linear regression analysis, t test, f test, coefficient of determination and test the value of the absolute difference. The result of the research shows that: leverage (Debt Equity Ratio) has no significant influence on CSR disclosure, liquidity (Current Ratio) has significant influence on CSR disclosure, institutional ownership can significantly moderate leverage and liquidity influence to CSR disclosure. Keywords: Leverage, liquidity, institutional ownership, CSR